The Effect of Vitamin C Addition in Andromed® Dilution on Procentage of Motility and Spermatozoa Intact Plasma Membrane of Aceh Bull After Freezing - Hasan Al Aslam; Dasrul Dasrul; Rosmaidar Rosmaidar (Jurnal Medika Veterinaria, 2014)
This study aimed to determine the effect of vitamin C addition in andromed® dilution on procentage of motility and intact plasma membrane post thawing of aceh bull spermatozoa. This research used fresh semen aceh bull were collected using artificial vagina and divided into four treatments.Control treatment (P0) semen without the addition of vitamin C, first treatment (P1) semen plus vitamin C 0.5 g/100 ml of dilution, second treatment (P2) semen plus vitamin C 1.0 g/100 ml of dilution, third treatment (P3) semen plus vitamin C 2.0 g/100 ml of dilution. The experiment design used was completely randomized design (CRD). Data was analyzed using ANOVA (Analysis of Variant) and followed by Duncan’s multiple range (Duncan’s Multiple Range Test) 5% confidence interval. The result showed that the addition of vitamin C influence the motility and intact plasma membrane percentage of aceh bull spermatozoa after thawing. The addition of vitamin C 0.5 g/100 ml and 1.0 g/100 ml increase motility and intact plasma membrane percentage, while vitamin C 2.0 g/100 ml decrease motility and intact membrane plasma percentage after thawing.Key words: intact plasma membrane, motility, aceh bull, spermatozoa, vitamin C